Japan's Arduous Rejuvenation as a Global Power Democratic Resilience and the US-China Challenge - Teo, Victor (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This open access book assesses the profound impact of Japan's aspirations to become a great power on Japanese security, democracy and foreign relations. Rather than viewing the process of normalization and rejuvenation as two decades of remilitarization in face of rapidly changing strategic environment and domestic political circumstances, this volume contextualizes Japan's contemporary international relations against the longer grain of Japanese historical interactions. It demonstrates that policies and statecraft in the Prime Minister Shinzo Abe's era are a continuation of a long, unbroken and arduous effort by successive generations of leaders to preserve Japanese autonomy, enhance security and advance Japanese national interests. Arguing against the notion that Japan cannot work with China as long as the US-Japan alliance is in place, the book suggests that Tokyo could forge constructive relations with Beijing by engaging China in joint projects in and outside of the Asia-Pacific in issue areas such as infrastructure development or in the provision of international public goods. It also submits that an improvement in Japan-China relations would enhance rather than detract Japan-US relations and that Tokyo will find that her new found automony in the US-Japan alliance would not only accord her more political respect and strategic latitude, but also allow her to ameliorate the excesses of American foreign policy adventurism, paving for her to become a truly normal great power.